Fish Consumption and Advisory Awareness among a Representative Sample of Wisconsin Adults, 2017–2019. Issue 4 (May 2023) - He, Xiaofei; Tomasallo, Carrie; Meiman, Jonathan
Purpose: To examine fish consumption patterns and fish advisory awareness among Wisconsin adults. Design: Cross-sectional data from population-based survey. Setting: 2017-2019 Wisconsin Behavioral Risk Factor Surveillance System (BRFSS), supplemental fish module. Subjects: 15, 757 Wisconsinites aged ≥18 years. Annual response rates ranged 46.1-53.3%. Measures: Fish consumption, advisory awareness, background and demographic characteristics. Analysis: Weighted binary and multinomial logistic regression. Results: Most Wisconsinites reported eating fish in the past 30 days, with approximately half (49.8%) consuming less than one fish meal per week. One-fifth of adults reported consuming sportfish. Women were less likely to eat any fish (PORadj = .6, 95% CI: .5-.7) and sportfish than men (PORadj = .7, 95% CI: .6-.8). The majority (76.7%) of sportfish consumers were aware of fish advisories. However, women (PORadj = .7, 95% CI: .5-.9) and black, Indigenous, and people of color (BIPOC) (PORadj = .4, 95% CI: .2-.7) sportfish consumers were less likely to be aware of fish advisories. Compared to adults aged 18-34 years, adults ≥55 years were twice as likely to eat 1-2 fish meals (vs. less than 1 fish meal) per week (PORadj = 2.3, 95% CI: 1.8-2.9). Conclusion: Findings indicate that half of all Wisconsinites consumed less fish than recommended by Wisconsin fish advisories, and women and BIPOC respondents were less likely to be aware of advisories. Educational efforts are needed to improve fish consumption habits.